2017
DOI: 10.1177/1179064417690543
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Her2/neu Expression in Gastrointestinal Stromal Tumors: Immunohistochemical Study

Abstract: Background:Gastrointestinal stromal tumor (GIST) is a relatively rare type of neoplasms. In Egypt, it represents 2.5% of gastrointestinal tumors and 0.3% of all malignancies. Most of the GISTs develop in the stomach.Aim:To reveal the significance of Her2/neu immunohistochemical expression in GIST and its correlation with other histopathologic parameters and tumor relapse after regular follow-up.Patients and methods:This study is a retrospective and prospective cohort. It included 32 patients with GISTs, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…ERBB2 is another upstream regulator observed to be upregulated in the metastatic samples and is a major driver of cell proliferation and angiogenesis. In a previous study, ERBB2 protein (Her2/neu) expression has been significantly correlated with risk grade, tumour size, mitotic count, and increased risk of relapse in primary GIST [ 61 ]. Overexpression of the upstream regulator MYC has previously been shown to reversibly induce and maintain CIN, contributing to aneuploidy, tumorigenesis, and tumour evolution [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…ERBB2 is another upstream regulator observed to be upregulated in the metastatic samples and is a major driver of cell proliferation and angiogenesis. In a previous study, ERBB2 protein (Her2/neu) expression has been significantly correlated with risk grade, tumour size, mitotic count, and increased risk of relapse in primary GIST [ 61 ]. Overexpression of the upstream regulator MYC has previously been shown to reversibly induce and maintain CIN, contributing to aneuploidy, tumorigenesis, and tumour evolution [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, another trial including 94 GIST failed to show gene amplification for HER2 [90]. However, a small Egyptian study including 32 patients showed a 43.7% positivity in HER2 status [91]. Additionally, it reported that high-risk grade, tumor size, mitotic count, and increased risk of relapse were significantly correlated with HER2 positivity.…”
Section: Gastrointestinal Stromal Tumors (Gist)mentioning
confidence: 99%